Pengaruh Media Sosial Terhadap Perubahan Makna Kata dalam Bahasa Gaul di Kalangan Mahasiswa/i PPKn Unimed - Della Pebriani Simamora; Grace Claudia Valerina Saragih; Kevin Cornelius Manurung; Salwa Khairani Tarigan; Vany Helpiana Saragih; Nurul Azizah (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This research is entitled "The Influence of Social Media on Changes in the Meaning of Words in Slang Among PPKn Unimed Students". This study analyzes how social media has a significant impact on the change of word meaning in slang which also affects the good and correct use of Indonesian. Therefore, understanding and knowledge related to this matter are needed today, especially among students. This research uses a qualitative method through a survey on Google Form which is distributed to PPKn Unimed students. The results of the study show that social media such as TikTok, Twitter and other social media have a great influence on the use of slang among students. Many students also argue that social media is the main source for students to find slang which is then used in daily life when talking or communicating with others. This study concludes that social media has a significant influence on changing the meaning of the word money can have an impact on good and correct Indonesian language skills, especially among students.